Legal Protection for Soybean Farmers in Cooperation Based on the Muzara'ah Akad with the Murabahah System - Susanti, Dyah Ochtorina; Efendi, A’an; Sari, Nuzulia Kumala (SASI, 2022)
Introduction: During the pandemic Covid-19, the global soybean market experienced a shock which resulted in the availability of imported soybeans in several countries decreasing and soybean prices increasing. This also has an impact on small and medium industries that cannot afford soybeans for their processed food raw materials, one of which is the production of “tempe”. Purposes of the Research: The purpose of this study is to explain the concept of cooperation to provide legal protection to soybean farmers based on a muzara'ah akad with a murabahah system. Methods of the Research: The research method used is normative legal research with a statute legal approach and a conceptual approach. Results of the Research: The result of this study include 2 (two) things, namely the concept of cooperation and the form of legal protection. The concept of cooperation consists of: The first scheme, cooperation between the government (Pemda) with soybean farmers and Islamic banks. The second scheme is the cooperation of Islamic banks with soybean farmers using a murabahah akad. The third scheme, namely cooperation between soybean farmers and cultivator using muzara’ah akad. In connection with the form of legal protection, it is divided into 2 (two) namely: first, external legal protection regulated in Law Number 19 of 2013 concerning Protection and Empowerment of Farmers, which was later changed to Law no. 11 of 2020 concerning Job Creation, and second, internal legal protection, namely 3 (three) concepts of cooperation as outlined in a written agreement as a form of guarantee of legal certainty for the parties, especially for soybean farmers.